Role of horseradish peroxidase in polypyrrole conductivity - Othman, Siti Amira; Radiman, Shahidan (Trans Tech Publications, 2017)
Immobilise enzymes can offer many advantages over their soluble forms making this is a topic of active research in enzyme technology for industrial applications. There are various methods for enzyme immobilization as well as support materials. The methods and supports used for immobilisation of certain enzyme are chosen to ensure the highest retention of activity and its stability. Enzyme Horseradish peroxidise (HRP) was used extensively in molecular biology applications primarily for its ability to amplify a weak signal and increase the detectability of a target molecules. Recently class of conducting polymers are used as a polymeric support. Among the family a conducting polymer, polypyrrole (PPY) has intensively been used for various reason because of its unique properties such as ease of synthesis by chemical or electrochemical oxidative polymerization of the monomers, role as a polymeric support and also have potential in various field . It has alternating single and double carbon-carbon bonds along the polymeric chains. The highly conjugated polymer chain can be assigned reversible chemical, electrochemical and physical properties controlled by a doping/ de-doping process, which makes this polymers very attractive as transducer materials in various sensing devices. This paper reports the process of immobilised enzymes on polymeric substrate and the role of enzymes in PPY conductivity. The characterization was done using UV-Visible, FTIR and four point probe